2019
DOI: 10.1137/18m118935x
|View full text |Cite
|
Sign up to set email alerts
|

DSOS and SDSOS Optimization: More Tractable Alternatives to Sum of Squares and Semidefinite Optimization

Abstract: In recent years, optimization theory has been greatly impacted by the advent of sum of squares (SOS) optimization. The reliance of this technique on large-scale semidefinite programs, however, has limited the scale of problems to which it can be applied. In this paper, we introduce diagonally dominant sum of squares (DSOS) and scaled diagonally dominant sum of squares (SDSOS) optimization as linear programming and second-order cone programming-based alternatives to sum of squares optimization that allow one to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
212
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(212 citation statements)
references
References 86 publications
0
212
0
Order By: Relevance
“…Proposition 2 demonstrates that even if the optimal choice of X is bounded in trace norm by a constant, the quality of Problem (2)'s approximation degrades with n. This result explains why various authors [21,13,1] have found that Problem (2) poorly approximates Problem (1) in a high-dimensional setting.…”
Section: A Linear Outer Approximationmentioning
confidence: 86%
“…Proposition 2 demonstrates that even if the optimal choice of X is bounded in trace norm by a constant, the quality of Problem (2)'s approximation degrades with n. This result explains why various authors [21,13,1] have found that Problem (2) poorly approximates Problem (1) in a high-dimensional setting.…”
Section: A Linear Outer Approximationmentioning
confidence: 86%
“…By combining this theorem with some linear algebraic observations, the authors show in [10] that optimization of a linear objective function over the intersection of the cone of dsos (resp. sdsos) polynomials of a given degree with an affine subspace can be carried out via linear programming (resp.…”
Section: Dsos and Sdsos Optimizationmentioning
confidence: 98%
“…In [10], the authors introduce "DSOS and SDSOS optimization" as linear programming and second-order cone programming-based alternatives to sum of squares and semidefinite optimization that allow for a trade off between computation time and solution quality. The following definitions are central to their framework.…”
Section: Dsos and Sdsos Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagonally dominant sum of squares (DSOS) and scaled diagonally dominant sum of squares (SDSOS) optimization as linear programming and second-order cone programming-based alternatives to sum of squares optimization that allow one to trade off computation time with solution quality. These are optimization problems over certain subsets of sum of squares polynomials [80]. In addition, applying different positivity certificates, such as Handelman's representation [69] and Krivine-Stengles certificate [81], will lead to linear program.…”
Section: Future Researchmentioning
confidence: 99%